2010
DOI: 10.1073/pnas.0912782107
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptors function as logic gates for nanoparticle binding and cell uptake

Abstract: More selective interactions of nanoparticles with cells would substantially increase their potential for diagnostic and therapeutic applications. Thus, it would not only be highly desirable that nanoparticles can be addressed to any cell with high target specificity and affinity, but that we could unequivocally define whether they rest immobilized on the cell surface as a diagnostic tag, or if they are internalized to serve as a delivery vehicle for drugs. To date no class of targets is known that would allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…In other work, Stadtman and Chock (1997) demonstrated that such a network can act as a flexible computational unit. Similar results were documented by Arkin and Ross (1994), and recently a number of researchers have developed these ideas (Hild et al 2010;Wang 2011).…”
Section: Introductionsupporting
confidence: 71%
“…In other work, Stadtman and Chock (1997) demonstrated that such a network can act as a flexible computational unit. Similar results were documented by Arkin and Ross (1994), and recently a number of researchers have developed these ideas (Hild et al 2010;Wang 2011).…”
Section: Introductionsupporting
confidence: 71%
“…This activity can alter the fate of NPs decorated with such peptides [273]. In this study, the targeting of quantum dots to G protein-coupled receptors using peptide agonists led to the internalization of the nanomaterial.…”
Section: Active Targeting: Toward Magic Bullet?mentioning
confidence: 93%
“…According to Cerdevall et al, the corona could alter biological functions by the high presence of proteins in a restricted cellular area (Cedervall et al 2007). Thereby, this complex may appear to the cell as an exogenous compound, leading to a recognition by G protein-coupled receptors, integrins, and Toll-like transmembrane receptors, acting as gateways to the cell and triggering the proinflammatory response (Hild et al 2010). Thus, due to the presence of a protein corona around them, NPs may 'mislead' the cells, which may recognize these NPs as pathogen-like invaders, such as lipopolysaccharides (LPS) originating from bacterial outer membranes.…”
Section: Mechanisms Of Uptake At Higher Dosementioning
confidence: 99%